2002
DOI: 10.2298/avb0206285k
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of insulin like growth factor-l and total protein in newborn calves offered different amounts of colostrums

Abstract: The aim of this investigation was to determine the concentrations of insulin like growth factor-I (IGF-I) and total protein in blood serum from calves consuming different amounts of colostrum during the first 32 h of postnatal life, as well as at 7 days old. The experiment involved two groups of calves. The first group was offered the standard amount of colostrum while the second group received half the recommended amount. At birth serum concentration of IGF-I was in the range from 5 to 13 nmol/L. Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…An increase in circulating IGF-I concentration in response to feeding occurs gradually: typically a significant increase above the fasting baseline requires at least 6 hours (Davis et al, 1996). Our previous results concerning serum IGF-I levels in newborn calves indicated that it is dependant on the amount of ingested colostrum (Kirovski et al, 2002). Our present study indicates that clinoptilolite treatment in newborn piglets effectively increases serum IGF-I concentration.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…An increase in circulating IGF-I concentration in response to feeding occurs gradually: typically a significant increase above the fasting baseline requires at least 6 hours (Davis et al, 1996). Our previous results concerning serum IGF-I levels in newborn calves indicated that it is dependant on the amount of ingested colostrum (Kirovski et al, 2002). Our present study indicates that clinoptilolite treatment in newborn piglets effectively increases serum IGF-I concentration.…”
Section: Discussionsupporting
confidence: 70%
“…This increase is consistent and less variable than the apparent increase in serum insulin concentration. Assuming that the amount of ingested colostrum is uniform in the treated and control group of piglets, the difference in the blood serum IGF-I concentrations could not be attributed to this factor, as was the case in our previous experiment in calves (Kirovski et al, 2002). However, we cannot exclude the possi-bility of greater endogenous synthesis of IGF-I in various tissues of the neonatal piglets.…”
Section: Discussionmentioning
confidence: 64%
“…Plasma proteins do not leave the vasculature readily (Armstrong et al, 1998), and therefore neonatal calves that ingest colostrum may have a corresponding level of plasma globulin and total protein, which is maintained beyond colostrum production of the cow. This is consistent with a study on neonatal calves that demonstrated a marked increase in serum protein concentration within two hours of feeding (Danijela et al, 2002).…”
Section: Observing and Quantifying Hydration Status In Neonatal Calvessupporting
confidence: 92%
“…In the same study, feeding of 3 or 1.5 litres of colostrum during the first 12 hours of life led to differences in serum protein concentration at 4 hours post-feeding (54.7 g/L and 42.7 g/L, respectively) and at day 7 of life (69.5 g/L and 60 g/L, respectively; Danijela et al, 2002). A limitation in the use of plasma protein or globulin concentration as an indicator of volume of colostrum uptake may be that there is decreasing efficiency of IgG absorption by calves, where every 30 minute delay of first colostrum decreases calf serum IgG concentration by about 2 mg/mL (Rajala and Castren, 1995).…”
Section: Observing and Quantifying Hydration Status In Neonatal Calvesmentioning
confidence: 81%
See 1 more Smart Citation